The Quality of Kampung Broiler (KB) Chicken Frozen Semen with DMA Concentrations on Yolk Lactate Ringer Diluent - J. Junaedi; Raden Iis Arifiantini; Cece Sumantri (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
Chicken Kampung Broiler (KB) is the result of a cross between a local chicken (chicken) with broiler imported chicken (broiler chicken). Testing the quality of frozen chicken semen from crossing needs to be done to get high productivity. This study aims to obtain a concentration of cryoprotectant Dimethyl Acetamide (DMA) the best of the concentration of 5%, 7% and 9% in chicken semen freezing KB. The semen used in this study came from three chickens of KB and repeated as many as nine times. Semen is collected by the method of message three times a week. Semen is evaluated macroscopically and microscopically. Subsequently spermatozoa were diluted with yolk diluent and the addition of three DMA cryoprotectant concentrations (5%, 7%, and 9%). Semen diluted 0:25 ml is packed into straw. Then equilibrated at a temperature of 5 ° C for two hours. After equilibration evaluation of motility and viability of spermatozoa. It is then frozen on liquid nitrogen vapor for 10 minutes. Frozen semen is then stored in liquid nitrogen containers at a temperature of -196 ° C. After 24 hours, the thawing semen in 37 ° C for 30 seconds. The results showed that the addition of DMA 9% in Ringer's lactate diluent yolk produces a percentage motility and viability after thawing is greater than 5% and DMA 7%. Neither the addition of DMA 9% concentration can increase recovery rate after thawing